Determination of fatigue crack propagation thresholds for steel in presence of environmental effects. (December 2021) - Madia, M.; Vojtek, T.; Duarte, L.; Zerbst, U.; Pokorný, P.; Jambor, M.; Hutař, P.
Graphical abstract: Highlights: Oxide-induced crack closure influences near-threshold crack propagation greatly. Lower stress ratios and higher absolute air humidity enhance oxide formation. Oxide formation and accumulation is larger in martensitic and bainitic steels. Oxide-products formation does not depend on the testing procedure. Optimal closure-free data are determined for stress ratio R  ≥ 0.8. Abstract: The experimental determination of the resistance to fatigue crack propagation in steel, particularly in the so-called near-threshold regime, is a crucial issue for safety-relevant components which are designed to operate for a large number of loading cycles before undergoing periodic inspections. This work summarizes the most relevant results of extensive experimental campaigns conducted at BAM and IPM over the last years, which have been devoted to the determination of fatigue crack propagation characteristics on medium and high strength steels. The influence of environment, oxide-induced crack closure and test methodologies in the near-threshold regime are discussed.